2013
DOI: 10.4161/rna.24908
|View full text |Cite
|
Sign up to set email alerts
|

Pentatricopeptide repeat proteins involved in plant organellar RNA editing

Abstract: C-to-U RNA editing has been widely observed in organellar RNAs in terrestrial plants. Recent research has revealed the significance of a large, plant-specific family of pentatricopeptide repeat (PPR) proteins for RNA editing and other RNA processing events in plant mitochondria and chloroplasts. PPR protein is a sequence-specific RNA-binding protein that identifies specific C residues for editing. Discovery of the RNA recognition code for PPR motifs, including verification and prediction of the individual RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 54 publications
1
52
1
Order By: Relevance
“…The PLS subfamily of PPR proteins recognizes distinct targets for RNA editing (6)(7)(8)(9)(10)(11). A number of PPR factors, including CRR4, CRR28, OTP80, and OTP82, and a DYW domain-containing protein, DYW1, are known to be involved in the editing of ndhB and ndhD transcripts (22)(23)(24)(25)(26), which we show in this study to contain editing sites severely affected in ppo1.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The PLS subfamily of PPR proteins recognizes distinct targets for RNA editing (6)(7)(8)(9)(10)(11). A number of PPR factors, including CRR4, CRR28, OTP80, and OTP82, and a DYW domain-containing protein, DYW1, are known to be involved in the editing of ndhB and ndhD transcripts (22)(23)(24)(25)(26), which we show in this study to contain editing sites severely affected in ppo1.…”
Section: Resultsmentioning
confidence: 91%
“…The current consensus RNA editing model predicts that PPR proteins specifically recognize cis elements near the target cytidine residue and provide a platform for molecular attachment of other editing factors, such as MORF proteins (1,7,10,11,35). MORFs act as bridges that physically link PPR or related proteins to PPO1 through specific regions (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Considering the nad2 transcript pattern in rpf7-1 and Chat-1, which both harbor RPF7 knockout alleles, and the nad2 RNA pattern in Can-0, we concluded that the latter accession also encodes a non-functional RPF7 gene, here caused by the presence of a premature translation stop codon within PPR motif P 6 . In summary these results strongly suggest that PPR motifs P 6 and P 7 are critical for RPF7 function in nad2 transcript maturation.…”
Section: 34mentioning
confidence: 99%
“…[1][2][3][4][5] In these organelles, PPR proteins specify cytidines to be converted to uridines by RNA editing. 6 PPR proteins involved in this process group into subclass PLS, according to their composition of canonical (P), short (S) and long (L) repeats. 7 PPR proteins are also involved in intron splicing as well as in 5′ and 3′ end formation of organellar transcripts.…”
Section: Introductionmentioning
confidence: 99%